Heteronormative classrooms under surveillance: Gay academics' concerns about addressing queer issues in China. Issue 1 (2nd January 2023) - Cui, Le
Abstract: Gay academics in China are governed by both the repressive political climate and heteronormative culture on campus. This intersectional experience is still underexplored in the literature on queer teachers. Drawing on 40 gay academics' interview narratives, this article focuses on their concerns about addressing queer issues in the classroom in Chinese universities. Heteronormativity is adopted as a theoretical concept to unpack the constitution of sexual culture on Chinese campuses. It is shown that heteronormativity operates in interpersonal interactions and institutional practices in universities. Given China's unique political context, this research highlights the impact of repressive politics on the perpetuation of heteronormativity. A range of classroom surveillance and censorship techniques operated by the authorities are revealed as constraining gay academics from addressing queer issues in class. It is argued that university classrooms in China are heteronormative spaces where queerness is silenced by the institutions and Party-state.